EXAMINING THE REGULATION OF INDEPENDENT PROCEDURE AT THE INDONESIAN INDUSTRIAL RELATIONS COURT - Kadek Agus Sudiarawan; Putu Ade Harriestha Martana (Kanun Jurnal Ilmu Hukum, 2022)
This study aims to examine whether the current industrial relations court procedural law system is sufficiently ideal as a reference for the settlement of industrial relations disputes in Indonesia and to test the urgency of regulating independent procedural law in the Court of Indonesian Industrial Relations. This is a normative legal research with a statutory approach, a conceptual approach and comparative approach. The result shows that the industrial relation court procedural law system is not ideal enough to accommodate the development and complexity of disputes that occur in Indonesian labor today. Simple, quick and inexpensive way of settling dispute is difficult to occur when the procedural law that is enforced still adopts or is unable to escape from HIR, RBg, RV as civil procedural law (colonial product), which has a general character. The Industrial Relations Court as one of the Special Courts must be able to show its independent character, including in regulating procedural law. Comparative studies with the state of Thailand, Malaysia and Japan are used in this paper in order to illustrate the importance of the regulation concerning the Industrial Relations Court procedures. Changes to the procedural law of the Industrial Relation Court are urgent to do in order to provide an effective and efficient means of dispute resolution that is able to represent simple, quick and inexpensive principles according to the needs or demands of workers and employers today